Perturbation of Intracellular Cholesterol and Fatty Acid Homeostasis During Flavivirus Infections - Pombo, Joao Palma; Sanyal, Sumana (Frontiers in Immunology, 2018)
Cellular lipid homeostasis is maintained through an intricately linked array of anabolic and catabolic pathways. Upon flavivirus infections, these are significantly altered: on the one hand, these viruses can co-opt lipid metabolic pathways to generate ATP to facilitate replication, or to synthesize membrane components to generate replication sites; on the other hand, more recent evidence suggests counter strategies employed by host cells, which actively modulate several of these networks in response to infection, enhancing interferon signaling by doing so, and thus creating an antiviral environment. In this review, we discuss recent data on mechanisms of alteration of lipid metabolic pathways during infection by flaviviruses, with a focus on cholesterol and fatty acid biosynthesis, which can be manipulated by the invading viruses to support replication, but can also modulated by the host immune system itself, as a means to fight infection.